Perianesthetic Management in a Patient With Alzheimer’s Disease Complicated With Pulmonary Infection Who Underwent Emergency Right Artificial Femoral Head Replacement Surgery: A Case Report and Review of the Literature - Wenying Song; Jing Huang; Ying Li; Jiajia Liu; Hui Ding (Case Reports in Infectious Diseases)
Conclusion: We utilized multidisciplinary consultation before the operation, attempted to improve the state of the patient before the operation, chose an appropriate anesthetic scheme during the operation, strengthened cardiopulmonary protections, and returned the patient to the ward safely after the operation; however, the patient did not recover well post operation.